In Vivo Confocal Microscopic Findings of Subepithelial Infiltrates Associated with Epidemic Keratoconjunctivitis - Sibel Kocabeyoğlu; Mehmet Cem Mocan; Murat İrkeç (Türk Oftalmoloji Dergisi, 2015)
Adenoviruses are the most common cause of viral conjunctivitis and may lead to severe morbidity due to corneal involvement. In this report, we aimed to describe the clinical and in vivo confocal microscopic (IVCM) findings of three patients with adenoviral keratoconjunctivitis. All patients had corneal subepithelial infiltrates as observed on slit lamp biomicroscopy. IVCM revealed hyperreflective inflammatory cells in the basal epithelium and the anterior stroma together with subepithelial infiltrations of dendritic cells. Subbasal nerves, posterior stroma, and endothelium showed normal morphology, reflectivity, and cellular density. (Turk J Ophthalmol 2015; 45: 119-121)